2015
DOI: 10.1007/s10067-015-2970-6
|View full text |Cite
|
Sign up to set email alerts
|

Severe vitamin D deficiency in patients with Kawasaki disease: a potential role in the risk to develop heart vascular abnormalities?

Abstract: Twenty-five-hydroxyvitamin D (25(OH)-vitamin D) is crucial in the regulation of immunologic processes, but-although its deficiency has been reported in patients with different rheumatological disorders-no data are available for Kawasaki disease (KD). The goals of this study were to assess the serum levels of 25(OH)-vitamin D in children with KD and evaluate the relationship with the eventual occurrence of KD-related vascular abnormalities. We evaluated serum 25(OH)-vitamin D levels in 79 children with KD (21 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 41 publications
2
52
0
2
Order By: Relevance
“…As was previously mentioned, vitamin D exerts its anti-inflammatory activity through several ways and its supplementation reduced inflammatory marker including IL-6 and CRP 3) . Another study 29) reported that low vitamin D levels increase coronary artery complications in KD and serum vitamin D concentration is negatively associated with ESR and CRP. However we did not observe any differences in the incidence of coronary artery complications, ESR, or CRP between the 2 groups.…”
Section: Discussionmentioning
confidence: 96%
“…As was previously mentioned, vitamin D exerts its anti-inflammatory activity through several ways and its supplementation reduced inflammatory marker including IL-6 and CRP 3) . Another study 29) reported that low vitamin D levels increase coronary artery complications in KD and serum vitamin D concentration is negatively associated with ESR and CRP. However we did not observe any differences in the incidence of coronary artery complications, ESR, or CRP between the 2 groups.…”
Section: Discussionmentioning
confidence: 96%
“…This may be the reason for the simultaneous attenuation of CRP and inflammatory cytokines (CD4(+) IFN-γ) in hemodialysis patients after calcitriol treatment [19], or elevation of both CRP and cytokines in severe COVID-19 patients [23]. The relationship between CRP and Vit D has been investigated in multiple clinical studies and demonstrating an inverse correlation between the two variables [16,50]. In the following we investigate the link between CRP and Vit D among different age groups and among subjects with low-income and high-income.…”
Section: Crp and Vit D Deficiency In Healthy Subjectsmentioning
confidence: 99%
“…8 Kawasaki syndrome, currently being reported with increasing incidence while countries are in 'lockdown', also has a winter predominance and here too a causative role for vitamin D deficiency has been suggested. 9 All the associations between vitamin D deficiency and COVID-19 severity are circumstantial but they are stacking up and obtaining more direct evidence will not be easy. If low serum vitamin D levels are found in patients with severe COVID-19 these could reasonably be attributed to the well-recognised negative acute phase reactant response of vitamin D to illness.…”
Section: Editorsmentioning
confidence: 99%